Kinetic Model for pH Variation Resulted from Interaction of Aqueous Solution Contaminated with Nickel Ions and Cement Kiln Dust. (29th April 2020) - Ahmed, Dooraid N.; Faisal, Ayad A. H.; Jassam, Salim H.; Naji, Laith A.; Naushad, Mu.
Abstract : Reaction term in the transport equation which described the migration of metal ions in the porous medium is frequently represented by conventional kinetic models such as pseudo-first order, pseudo-second order, and others. Unfortunately, these models are applicable for the constant value of solution pH, and they cannot simulate the real situation in the field scale where this pH may be changed with time. Accordingly, the present study is a good attempt to derive the kinetic model that can simulate the change in the pH of the solution through solute transport. This was achieved by modifying the adsorption capacity and reaction constant to be functions in terms of solution pH by using semianalytical analysis and numerical approximation. The results proved that the kinetic model based on the numerical approximation (using exponential functions for adsorption capacity and reaction constant) symbolled as model 2 was more representative from other models applied for the description of interaction of nickel ions (with initial concentration of 400 mg/L) and cement kiln dust with sum of squared error ≤1.54913 and determination coefficient ≥0.889. Also, the developed models had high ability for recognizing between pure precipitation and pure adsorption.